Religious Moderation and Social Transformation Ideas: Realizing the Khaira Ummah in an Era of Disruption - Ezar Amrullah; Abdul Manan (STAIFAS-Press, 2023)
The current era of disruption has changed the perspective and behavior of humans in their lives, including in religion. The way of religion in the current era cannot be separated from exclusive religious patterns so that the potential for social friction becomes a major problem. Digital space as a nomenclature for the era of disruption that should be able to accelerate social cohesion, however, in fact has not been used a little as a forum for provoking religious sentiments. This then encourages research related to religious moderation that is increasingly needed. This research was conducted using the literature study method to explore the messages of the Qur'an which discuss the idea of ​​social transformation. The results of the research succeeded in uncovering the message of the Qur'an contained in QS. Ali-Imran verse 110 and QS. Al-Hadid verse 25 in constructing transformative ideas.